Regeneration of multiple shoots from the callus cultures of Sauropus androgynous (L.) Merr. - S. Padma, D. H. Tejavathi (Journal of Phytology, 2015)
Morphogenetic potential of shoot tip, leaf and nodal explants of Sauropus androgynous was investigated to develop a reliable plant regeneration protocol via indirect organogenesis. Explants were cultured on Murashige and Skoog’s (MS) medium and Phillips & Collins (L2) medium supplemented with different concentrations of BAP either alone or in combinations with other auxins such as IAA, NAA, 2,4-D and IBA along with GA3. However, L2 medium with hormones was found to be more supportive for induction of profuse callus and subsequent regeneration of shoot buds than the same hormonal composition of MS medium. Maximum number of shoots per culture were differentiated from the organogenic callus raised on L2 + BAP (13.20 µM) + IAA (11.42 µM) + GA3 (1.44 µM). Thus regenerated shoots were rooted on ½ L2 + IAA (2.85 µM). The plantlets were acclimatized for 3-4 weeks in pearlite before transferring them into pots containing soil, sand and manure in 1:1:1 ratio. Nearly 90% of survival was recorded.